Pengaruh Baby Spa (Solus Per Aqua) Terhadap Kualitas Tidur Bayi Usia 3-12 Bulan - Husnul Khatimah; Muammar; Rohana (STIKes Darussalam Lhokseumawe, 2019)
Prevalence data in Indonesia is around 10%, approximately 28 million of the total 238 million Indonesian population suffer from sleep deprivation. In Indonesia, quite a lot of babies have sleep problems, which is around 44.2% of babies experience sleep disorders such as frequently waking up at night. The purpose of this study was to determine the effect of Baby Spa (Solus Per Aqua) on the sleep quality of infants aged 3-12 months at Zieyata Baby Spa Clinic, Meunasah Tgk Village, Gadong District, Juang City District, Bireuen Regency. SPA means doing body treatments with water as a medium. This research is analytic with cross sectional study approach. This research was carried out at the Zieyata Baby Spa (Solus Per Aqua) Clinic, Meunasah Tgk Village, Gadong District, Kota Juang Regency, Bireuen Regency from January 10 to September 18, 2019. The population was all mothers and babies at the Zieyata Baby Spa Clinic, Meunasah Village Tgk Di Gadong, Kota Juang District, Bireuen Regency, totaled 52 people, data for July 2019. The sampling technique was a total sampling of 52 mothers. The results of the univariate test showed that most of the baby spas were in the non-routine category (53.8%) and the sleep quality of infants aged 3-12 months was mostly in the poor category (59.6%).